THE INFLUENCE OF THE TECHNOLOGICAL PARAMETERS ON THE CHARACTERISTICS OF CAST DENTAL BRIDGES - Norina Forna; Monica Tatarciuc; Anca Vitalariu; Raluca Baciu; Diana Diaconu Popa (Romanian Society of Oral Rehabilitation, 2019)
The dental bridges have a non metallic element made up in ceramic or composite that will rehabilitate the morphology and the functions, and a metallic framework, that assure the resistance and the retention of the aesthetic component. The technological algorithm used in order to obtain cast prostheses has the following steps: pouring the casts, the wax patterns, investing and realization of the mold, dental alloy melting and casting, divesting and polishing. The aim of our study was to emphasize the technological steps that can influence the final parameters of the cast prostheses. Twenty-one metallic frameworks for different dental fixed prostheses were cast (crowns, short bridges and the full arch bridges) and evaluated through the macroscopic examination method in order to detect any possible surface defects (pores, fissures, fractures, holes or excesses of alloy). In conclusion, the accuracy of the technological parameters will prevent any errors and will lead to dental cast prostheses with optimal biomechanical and clinical behavior